Effectiveness of Math Universe on Students’ Combinatorics Understanding for Mathematics Olympiad Preparation - Ayufauziyah, Nur; Utami, Anita Dewi; Suwarman, Ramdhan Fazrianto (Jurnal Pendidikan Edutama, 2026)
Mathematics olympiads require higher-order thinking skills, logical reasoning, and mastery of non-routine material, one of which is combinatorics, a topic often considered difficult by students. Limitations in face-to-face coaching have encouraged the need for structured independent learning media that align with the characteristics of olympiad problems. This study aims to examine the effectiveness of the Math Universe application on students’ conceptual understanding of combinatorics in mathematics olympiads. The study employed a quantitative approach with a one-group pre-test–post-test design. The research subjects consisted of 40 students who were members of the Komunitas Pecinta Matematika (KPM). The research instrument was an olympiad-level combinatorics test administered before and after the use of the Math Universe application. Data were analyzed using a paired sample t-test. The results showed a significant difference in learning outcomes before and after the use of the Math Universe application. These findings indicate that Math Universe is effective in improving combinatorics learning outcomes through independent learning based on self-directed learning and mobile learning. This application has the potential to serve as a supporting medium for mathematics olympiad training, particularly for materials with a high level of complexity.